Methane Emissions From Nordic Seagrass Meadow Sediments - Asplund, Maria E.; Bonaglia, Stefano; Boström, Christoffer; Dahl, Martin; Deyanova, Diana; Gagnon, Karine; Gullström, Martin; Holmer, Marianne; Björk, Mats (Frontiers in Marine Science, 2022)
Shallow coastal soft bottoms are important carbon sinks. Submerged vegetation has been shown to sequester carbon, increase sedimentary organic carbon (Corg) and thus suppress greenhouse gas (GHG) emissions. The ongoing regression of seagrass cover in many areas of the world can therefore lead to accelerated emission of GHGs. In Nordic waters, seagrass meadows have a high capacity for carbon storage, with some areas being recognized as blue carbon hotspots. To what extent these carbon stocks lead to emission of methane (CH4) is not yet known. We investigated benthic CH4 emission (i.e., net release from the sediment) in relation to seagrass (i.e. Zostera marina) cover and sedimentary Corg content (%) during the warm summer period (when emissions are likely to be highest). Methane exchange was measured in situ with benthic chambers at nine sites distributed in three regions along a salinity gradient from ∼6 in the Baltic Sea (Finland) to ∼20 in Kattegat (Denmark) and ∼26 in Skagerrak (Sweden). The net release of CH4 from seagrass sediments and adjacent unvegetated areas was generally low compared to other coastal habitats in the region (such as mussel banks and wetlands) and to other seagrass areas worldwide. The lowest net release was found in Finland. We found a positive relationship between CH4 net release and sedimentary Corg content in both seagrass meadows and unvegetated areas, whereas no clear relationship between seagrass cover and CH4 net release was observed. Overall, the data suggest that Nordic Zostera marina meadows release average levels of CH4 ranging from 0.3 to 3.0 μg CH4 m–2 h–1, which is at least 12–78 times lower (CO2 equivalents) than their carbon accumulation rates previously estimated from seagrass meadows in the region, thereby not hampering their role as carbon sinks. Thus, the relatively weak CH4 emissions from Nordic Z. marina meadows will not outweigh their importance as carbon sinks under present environmental conditions.